Avaliação da arborização urbana : estudo de caso a cidade de Cruz Alta - RS - Raguzoni, Luis Antonio Teixeira (2011)
This research seeks theoretical and methodological elements for the economic value of urban trees. It is determined to study the subject of a General Chamber Street area via major structural city of Cruz Alta / RS. The methodology for the diagnosis, had several techniques such as: characterization of the object of study with archival research, to characterize the morphology of tree species of sectors A and B of the General Chamber Street; check the compatibility of those trees with the network infrastructure; survey of user opinion on the degree of satisfaction of sectors, raising the measurements of the variables of temperature and relative humidity caused by afforestation in the search space; Helliwell apply the method as a tool to assess economic sectors of the trees A and B General Chamber Street in Cruz Alta - RS. Justifies the choice of subject of study by insufficient information about valuation of trees in urban areas in Brazil, because the existing research began in Europe in the 1960s, such as the research Helliwell. Observed in Case Study disability accessibility, incompatibility of these trees with the networks of urban infrastructure by the lack of initial planning. Finally, examples of application of the method in which Helliwell indicates six factors for economic valuation of urban trees. Explaining the use of various methods and the lack of illuminating survey of the trees in the city of Cruz Alta - RS. Thus, it is intended to provide the data collected and the results of the Helliwell method for economic valuation of urban trees. With these results presented provide discussions on the subject of proposals to support future planning, management and cost management of urban trees